In situ damage precursor detection in fiber reinforced composites using anthracene-based mechanophore. (16th October 2019) - Koo, Bonsung; Miller, Jack; Gunckel, Ryan; Hall, Asha; Dai, Lenore; Chattopadhyay, Aditi
Abstract: A pioneering approach to in situ damage precursor detection in fiber reinforced polymer composites is developed using anthracene-based stress-sensitive mechanophore material. In this research, the anthracene-based mechanophore, which emits ultraviolet (UV) excited fluorescence on chemical bond breakage under the influence of external mechanical loads, is effectually used as a nanoscale damage sensor. Dimeric 9-anthracene carboxylic acid (Di-AC) is synthesized and incorporated into glass fiber reinforced polymer (GFRP) composites through a hand layup process. A quasi-static uniaxial tensile load is applied to the specimens, and UV excited fluorescence from the activated Di-AC mechanophore during the tensile loading tests is captured through UV camera. The results indicate that the activation of Di-AC starts at a very early stage in the tests (≈0.33% strain for single-ply and ≈0.5% strain for three-ply laminate specimens) and exhibits a linear increase prior to failure (≈1.6% strain for single-ply and ≈2.28% strain for three-ply laminate specimens). Nonlinear optical response is captured when the specimen is close to failure. The mechanophore response to interlaminar damage is also investigated using composite specimens with induced delamination. The potential of anthracene-based mechanophore for early damage detection as well as barely visible damage detection in GFRP is successfully demonstrated.